Perception differences of altered dental esthetics by dental professionals and laypersons - Mayuri Thomas; Rajesh Reddy; B Jayabharath Reddy (Wolters Kluwer Medknow Publications, 2011)
Background: When we smile, our smile could often become the target of close scrutiny by the person you are smiling at. A trained eye readily detects any asymmetricity or any aspect of that smile which may be out of balance, or disharmonious with its environment. The purpose of this study was to determine whether any such asymmetric or symmetric dental discrepancies were detectable by various groups of evaluators. Aims: The aim was to determine whether asymmetric and symmetric anterior dental discrepancies were detectable by orthodontists, general dentists, and laypersons, and to establish threshold levels for several specific aesthetic criteria that could be used by orthodontists and general dentists as an aid in the treatment planning. Materials and Methods: Three images of smiles were intentionally altered with a software-imaging program. The alterations involved the crown length, crown width, midline diastema, and the papillary height of the maxillary anterior teeth. These altered images were then rated by groups of general dentists, orthodontists, and laypersons using a visual analog scale. Statistical analysis of their responses resulted in the establishment of threshold levels of attractiveness for each group. Results: The orthodontists were more critical than the general dentists and laypersons when evaluating asymmetric crown length discrepancies. All three groups could identify a unilateral crown width discrepancy of 2.0 mm. A small midline diastema was not rated as unattractive by any group. Reduction of papillary height was generally rated as less attractive. Conclusions: Asymmetric alterations make teeth more unattractive not only to the dental professionals, but also to laypersons.